Pura Pucak Bukit Sinunggal Sebagai Daya Tarik Wisata Spiritual - Mahardika, Gede; Agus Nova, Ketut (Jurnal Penelitian Agama Hindu, 2023)
Bali as a tourist attraction has tremendous potential to be developed as a tourist attraction, one of which is a spiritual tourist attraction. The many temples in Bali can be developed as a spiritual tourism attraction, one of the famous temples is Pucak Bukit Sinunggal Temple which is in Tajun Village, Buleleng Regency. The purpose of this research is to identify the potential for spiritual tourism with SWOT analysis at Pucak Bukit Sinunggal Temple. This research was conducted using a qualitative descriptive approach with swot analysis with data collection techniques using observation, interviews and documentation. With the research location at Pucak Bukit Sinunggal Temple, Tajun Village, Kubutambahan District, Buleleng Regency. The results of this study indicate that the sacred area of ​​Pucak Bukit Sinunggal Temple is located on the main mandala which is bordered by a wall of penyengker which is located on Pucak Bukit Sinunggal. The potential attraction of spiritual tourism consists of physical and non-physical attractions. Physical attractiveness can be seen from the temple building or pelinggih, while non-physical potential can be seen from the status of the temple as a public temple, religious activities carried out at Pucak Bukit Sinunggal Temple such as piodalan, galungan, brass, siwalatri and meajar-ajar ceremonies. Aspects of the strength of Pucak Bukit Sinunggal Temple as a spiritual tourist attraction such as, the famous history of the temple, geographical location, temple status, cleanliness of the temple area, adequate security and good accessibility. While the aspects of weakness are lack of accommodation, less parking area, information facilities not yet available, lack of public awareness of spiritual tourism and not yet registered with the tourism agency. The conclusions from this study include that the main mandala is the sacred area of ​​Pucak Bukit Sinunggal Temple, physical and non-physical potential is a spiritual tourism attraction, there are several opportunities that need to be developed and weaknesses that need to be fixed.